PENGARUH TINDAKAN SUPERVISI DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA AUDITOR - Nur Hasniwati; Nur Khamisah (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2019)
This study entitled Effects of Measures for Supervision and Work Motivation Job Satisfaction Auditor (Empirical Study on the Audit Board of the Republic of Indonesia Representative Jambi Province). The purpose of this study was (1) to provide empirical evidence of the effect of partially between measures of supervision on job satisfaction of the Supreme Audit Agency (BPK) RI Representative Jambi Province (2) to provide empirical evidence of the effect of partially between work motivation on job satisfaction of auditors Agency (BPK) RI Representative Jambi Province (3) to provide empirical evidence of the simultaneous influence between action supervision and motivation on job satisfaction of the Supreme Audit Agency (BPK) RI Representative Jambi Province.. (1) supervision actions have a significant effect on auditor job satisfaction (2) work motivation does not have a significant effect on auditor job satisfaction (3) supervision actions and work motivation simultaneously have a significant effect on auditor job satisfaction (4) the magnitude of the effect of actions supervision and work motivation with job satisfaction of 36.5%, while the remaining 63.5% is influenced or explained by other variables not included in this research model. So it can be said to have a very strong cohesion coefficients.